THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND NURSING WORK EFFICIENCY AT KING FAHAD SPECIALIST HOSPITAL – QASSIM CLUSTER 2026 - Hanan Saad A; Alayed Alayed; Hafizah Che Hasan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Improving the quality of modern healthcare services largely depends on the effectiveness and efficiency of nursing personnel as the frontline providers of patient care. The complex and high-pressure work environment of specialized hospitals requires nurses to cope with emotional demands, heavy workloads, and rapid decision-making in critical situations. These conditions make emotional intelligence one of the important psychological factors influencing nursing performance quality. This study aimed to analyze the relationship between emotional intelligence and nursing work efficiency at King Fahad Specialist Hospital – Qassim Cluster, Saudi Arabia, in 2026. This study employed a quantitative approach with a cross-sectional design. The study population consisted of all active nurses working at King Fahad Specialist Hospital, Qassim Health Cluster. A total of 312 nurses were selected using stratified random sampling. Data were collected using the Emotional Intelligence Scale and Nursing Work Efficiency Scale, both of which had been tested for validity and reliability. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results revealed that emotional intelligence had a positive and significant effect on nursing work efficiency, with a path coefficient of 0.642, t-statistics of 9.871, and p-value < 0.001. The R-square value of 0.58 indicated that emotional intelligence explained 58% of the variance in nursing work efficiency. Emotional regulation and empathy emerged as the dominant indicators contributing to improved communication quality, clinical decision-making, and patient care effectiveness. This study concludes that emotional intelligence is an important psychological resource in improving nursing work efficiency in specialized hospitals. The findings strengthen the Job Demands–Resources (JD-R) Theory and Emotional Intelligence Theory in explaining the relationship between psychological resources and nursing performance. This study is expected to provide theoretical contributions to the development of nursing management literature and practical contributions for hospitals in designing healthcare human resource development strategies based on psychological well-being.